Investigating teachers’ pedagogical competence: A case study of professional digital competence application in Indonesia - Nur, Maulidia Rachmawati; Bahtiar, Muhamad Rizky; Umam, Amalul; Nurmayasari, Eva (Universitas Islam Sultan Agung, 2025)
In the current Indonesian educational landscape, technological aids hold important roles in promoting effective teaching and learning. This research addresses the critical need to understand teachers' proficiency levels in Professional Digital Competence (PDC) to navigate this digital shift. Teachers' capacity to implement innovative and relevant teaching strategies is essential in a time when information and communication technology (ICT) is becoming an increasingly essential component of education. The purpose of this study is to find out which competency level teachers are in PDC. It also aims to understand the implications of teachers’ PDC level for learning. Framed under a case study research design, this study administered questionnaires and interviews to five high school English teachers. The data collected were analyzed using thematic analysis. The findings showed that the level of teachers’ PDC varies among the participants, which leads the teachers to improve their effectiveness and efficiency in teaching by personalizing the learning processes and promoting more student-centered learning.